Legal Analysis Of Corruption And Social Change - Yudi, Permai; Berlian, Berlian (Jurnal Ilmu Sosial Mamangan, 2025)
Corruption is a critical issue that hampers development in many countries, including Indonesia. Its effects are not confined to economic losses but extend to societal, political, and legal structures. Corruption undermines democratic processes by allowing individuals or groups with money and power to influence elections, policy-making, and the judiciary, often at the expense of public interest. This distorts representation and diminishes public confidence in democratic systems. In societies where corruption becomes normalized, it can lead to a cultural acceptance of unethical behavior, diminishing the importance of honesty, fairness, and accountability. This can have long-term negative effects on the moral fabric of society, especially for younger generations. This article examines the relationship between anti-corruption laws and social change, focusing on how legal frameworks can be utilized as instruments for reducing corruption. Using a qualitative descriptive approach, this analysis explores how Indonesia’s anti-corruption laws and their enforcement impact the broader social dynamics. The conclusion drawn is that while legal measures are essential, significant social transformation is still required to combat corruption effectively.